ANALISIS PENGARUH FAKTOR PRODUKSI TERHADAP KESEJAHTERAAN PETANI MELALUI PRODUKSI JAGUNG DI KAMPUNG NAENA MUKTIPURA KABUPATEN MIMIKA - Haruna Rumalean; Gus Pujiriyono; Rahmat Arapi (ADISAM PUBLISHER, 2025)
This study aims to determine the effect of land area, capital, fertiliser, seeds, and farmer experience on farmer welfare through corn production in Naena Muktipura Village (SP VI), both directly and indirectly. The method used by the researcher is the associative method. The data collection technique used by the researcher was to distribute questionnaires to 50 respondents. The analytical tool used in this study was Path Analysis with the help of IBM SPSS v22. The results showed that land area, fertiliser, and farmer experience had a significant effect on corn production in Naena Muktipura Village, while capital and seeds did not have a significant effect on corn production in Naena Muktipura Village. Land area and capital had a significant effect on the welfare of farmers in Naena Muktipura Village, while fertiliser, seeds, farmer experience and production had no significant effect on the welfare of farmers in Naena Muktipura Village. Land area and farmer experience have a significant effect on farmer welfare through corn production in Naena Muktipura Village, while capital, fertiliser, and seeds have no significant effect on farmer welfare through corn production in Naena Muktipura Village, Mimika Regency.